2020
DOI: 10.1080/07391102.2020.1777904
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing cefuroxime for treatment of COVID-19: a scoping review of in silico studies

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), the causative agent of Coronavirus disease 19 , is a novel human Coronavirus that is responsible for about 300,000 deaths worldwide. To date, there is no confirmed treatment or vaccine prevention strategy against COVID-19. Due to the urgent need for effective treatment, drug repurposing is regarded as the immediate option. Potential drugs can often be identified via in silico drug screening experiments. Consequently, there has been an explosion of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 71 publications
1
37
0
3
Order By: Relevance
“…Accordingly, there has been a blast in drug repurposing experiments to invent innovative medicines as aspirants and research studies regarding circumstantial findings. One second-generation cephalosporin -Cefuroxime has been spotted with quite a lot of anecdotal benefits in the treatment of COVID-19 [51]. In that way, one scoping review reported that cefuroxime reveals promising efficacy in opposing three significant COVID-19 proteins necessary for replication in drug repurposing experimentations.…”
Section: Computational Drug Repurposing and Repositioningmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, there has been a blast in drug repurposing experiments to invent innovative medicines as aspirants and research studies regarding circumstantial findings. One second-generation cephalosporin -Cefuroxime has been spotted with quite a lot of anecdotal benefits in the treatment of COVID-19 [51]. In that way, one scoping review reported that cefuroxime reveals promising efficacy in opposing three significant COVID-19 proteins necessary for replication in drug repurposing experimentations.…”
Section: Computational Drug Repurposing and Repositioningmentioning
confidence: 99%
“…In that way, one scoping review reported that cefuroxime reveals promising efficacy in opposing three significant COVID-19 proteins necessary for replication in drug repurposing experimentations. In this manner, cefuroxime possibly possesses auspicious multi-target pharmacodynamics that can help us to combat the current pandemic [51]. Additionally, cefuroxime was approved by the US FDA in 1998.…”
Section: Computational Drug Repurposing and Repositioningmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus contains singlepositive-strand RNA (ribonucleic acid) genome protected by the four structural proteins named as nucleocapsid (N), matrix (M), envelope (E), and spike (S) (Durojaiye et al, 2020). In the last two decades, two mutated coronaviruses cause severe epidemics named as middle east respiratory syndrome coronavirus (MERS-CoV) and severe acute respiratory syndrome coronavirus (SARS-CoV) (de Wit et al, 2016;Wahedi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 has a genome of ~ 30 kb and is responsible for encoding the whole proteome of the pathogen. Both the structural and non-structural protein-coding region and accessory protein-coding region are the major parts of the intact coding RNA [13]. The four structural proteins constituting the main envelope of the virus, and eight accessory proteins are encoded by the genes located on the 3′-terminus.…”
Section: Introductionmentioning
confidence: 99%